A preliminary investigation of microsatellite-based genotyping in Trichomonas vaginalis - Prokopi, Marianna; Chatzitheodorou, Theodoros; Ackers, John P; Clark, C Graham (My University, 2011)
The genetic epidemiology of Trichomonas vaginalis is poorly understood at present. The recent release of the organism's genome sequence opens the way to investigation of polymorphic markers allowing strain identification. We here report a preliminary analysis of microsatellite loci in T. vaginalis and show that this approach holds promise for future studies of infection transmission and organism diversity.
Keywords: Diversity; Microsatellite; Trichomonas vaginalis